A critical political ecology of human dimensions of climate change: Epistemology, ontology, and ethics. (18th May 2018) - Goldman, Mara J.; Turner, Matthew D.; Daly, Meaghan
Abstract : To understand the broader epistemological and ontological politics of human dimensions of climate change, this review adopts a political ecology approach, informed by Science and Technology Studies concepts and research on multiple ontologies. We are particularly interested in assessing critical approaches to climate change knowledge as related to adaptation policies. The review addresses three specific areas where more critical engagement could help move debates about knowledge politics in human dimensions research forward in fruitful ways: first, discourse and a focus on the language used to talk about and reflect on human dimensions of climate change; second, co‐production and the troubling proliferation of depoliticized "instrumental" co‐productions of knowledge for adaptation; and third, the emerging literature on multiple ontologies exposing multiple enactments of climate change processes. We review each of these areas of literature, highlighting where more direct engagement with epistemological, ontological, and ethical questions is underway. In doing so, we subject the knowledge and practices that underlie dominant understandings of climate change to critical political ecology scrutiny. This article is categorized under: Social Status of Climate Change Knowledge > Sociology/Anthropology of Climate Knowledge Abstract : How do people experience and know the climate, what is considered valid knowledge about climate change, and what does this all mean for adaptation planning? This review outlines the politics involved in discussing knowledge for climate change adaptation, and points to emerging literature to critically address such knowledge politics.